The Quality of Bureaucracy and Capital Account Policies - Bai, Chong-En; Wei, Shang-Jin (World Bank, Washington, DC, 2014)
The extent of bureaucracy varies extensively across countries, but the quality of bureaucracy within a country changes more slowly than economic policies. The authors propose that the quality of bureaucracy may be an important structural determinant of open economy macroeconomic policies - especially the imposition or removal of capital control. In their model, capital controls are an instrument of financial repression. They entail efficiency loss for the economy but also generate implicit revenue for the government. The results show that bureaucratic corruption translates into the government's reduced ability to collect tax revenues. Even if capital controls and financial repression are otherwise inefficient, the government still has to rely on them to raise revenues to provide public goods. Among the countries for which the authors could get relevant data, they find that the more corrupt ones are indeed more likely to impose capital controls, a pattern consistent with the model's prediction. To deal with possible reverse causality, they use the extent of corruption in a country's judicial system, and the degree of democracy, as the instrumental variables for bureaucratic corruption. The instrumental variable regressions show the same result: more corrupt countries are associated with more severe capital controls. The results suggest that as countries develop and improve their public institutions, reducing bureaucratic corruption over time, they will choose to gradually liberalize their capital accounts. Removing capital controls prematurely when forced by outside institutions to do so could reduce rather than improve their economic efficiency.